2020
DOI: 10.1177/2158244020962777
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive and Supportive Mechanisms for Female Directors’ Risk-Averse Behavior: Evidence From South Asian Health Care Industry

Abstract: This article aims to understand the impact of gender diversity on a firm’s equity volatility along with the moderating effect of chief executive officer (CEO) pay–performance sensitivity, institutional activism, and corporate social responsibility (CSR) activities. The sample consists of 200 South Asian health care firms over the period 2010 to 2018. After confirming the prevalence of endogeneity, we rely on the results of system generalized method of moments (GMM) rather than any static model. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 116 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…Prior studies favor System GMM over Difference GMM due to its ability to estimate models simultaneously in both first differences and levels (Sila et al., 2016; Yahya et al., 2020). It allows the estimator to use more valid and powerful instrumental variables to mitigate the dynamic endogeneity (Roodman, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies favor System GMM over Difference GMM due to its ability to estimate models simultaneously in both first differences and levels (Sila et al., 2016; Yahya et al., 2020). It allows the estimator to use more valid and powerful instrumental variables to mitigate the dynamic endogeneity (Roodman, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, to test the robustness of the results, we performed additional estimations. First, considering that the use of the lagged dependent variable as a regressor could cause autocorrelation problems, a second-order generalized method of moments (GMM) model was used in order to deal simultaneously with endogeneity and autocorrelation problems ( Arellano and Bover, 1995 ; Yahya et al, 2020 ). Second, we applied lagged fixed effects using the Blau index as a proxy for gender diversity on the board, with the intention of isolating the causal relationship between this variable and risk ( Adams and Ragunathan, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies on companies in the United States ( Baixauli-Soler et al, 2015 ; Hurley and Choudhary, 2020 ), China ( Jebran et al, 2020 ), South Asia ( Yahya et al, 2020 ), Canada ( Chakraborty et al, 2019 ), Italia ( Rossi et al, 2017 ), and the U.K. ( Jizi and Nehme, 2017 ) found that the percentage of female board members shows a negative relationship with the total risk of the company’s shares in the stock market. Analogous results are found in two studies conducted on a sample of international banks ( Birindelli et al, 2020 ) and a sample of banks in the Arabian Gulf States ( Abou-El-Sood, 2019 ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“… 82 We ensured the validity of instruments through the Hansen- J test while the insignificant AR(2) test shows that model may not suffer from second-order autocorrelation. 85 There is also no issue of instrument proliferation as the number of instruments is less than the number of groups. 86 Since our study combines macro-level and firm-level data, GMM is also appropriate for such types of datasets.…”
Section: Methodsmentioning
confidence: 99%